2009
DOI: 10.1016/j.nbd.2009.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high fat diet on Morris maze performance, oxidative stress, and inflammation in rats: Contributions of maternal diet

Abstract: This study was undertaken to investigate the effects of prenatal and postnatal exposure to high fat diet on the brain. Female rats were divided into high fat diet (HFD) and control diet (CD) groups 4 weeks prior to breeding and throughout gestation and lactation. After weaning, male progeny were placed on a chow diet until 8 weeks old, and then segregated into HFD or CD groups. At 20 weeks old, rats were evaluated in the Morris water maze, and markers of oxidative stress and inflammation were documented in bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
166
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(177 citation statements)
references
References 101 publications
(123 reference statements)
9
166
1
1
Order By: Relevance
“…These findings are consistent with our previous evidence showing that 12 weeks of HFD consumption in rats caused brain mitochondrial dysfunction (Pipatpiboon et al 2012). Previous studies as well as our findings suggest that the cognitive impairment caused by long-term HFD consumption could be related to brain mitochondrial dysfunction and oxidative stress , Stranahan et al 2008, White et al 2009, Pintana et al 2012. Interestingly, we found that both vildagliptin and sitagliptin completely restored brain mitochondrial function and improved learning and memory behaviors in rats with HFD-induced insulin resistance.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with our previous evidence showing that 12 weeks of HFD consumption in rats caused brain mitochondrial dysfunction (Pipatpiboon et al 2012). Previous studies as well as our findings suggest that the cognitive impairment caused by long-term HFD consumption could be related to brain mitochondrial dysfunction and oxidative stress , Stranahan et al 2008, White et al 2009, Pintana et al 2012. Interestingly, we found that both vildagliptin and sitagliptin completely restored brain mitochondrial function and improved learning and memory behaviors in rats with HFD-induced insulin resistance.…”
Section: Discussionsupporting
confidence: 93%
“…Studies from our laboratory and others' have demonstrated that HFDs exacerbate tissue dysfunction in aging animals (11,29,46,68,76). Additionally, studies from our laboratory and others' have shown that HFDs promote much greater amounts of adipose gain, and presumably adipose tissue dysfunction, compared with younger animals (46,50,66).…”
Section: Discussionmentioning
confidence: 72%
“…Mice were fasted overnight and euthanized by isoflurane anaesthesia followed by rapid decapitation. Subcutaneous (inguinal) and visceral fat pads (epididymal) were manually dissected as described previously (68).…”
Section: Methodsmentioning
confidence: 99%
“…Evidence is emerging that the weight of the pregnant dam can increase dentate gyrus lipid peroxidation and impair neurogenesis in her offspring (160). Rats that were kept on a high-fat diet after being born to dams on high-fat diets had increased susceptibility to memory impairment and increase oxidative stress compared with rats that were either kept on a high-fat diet after being birthed by a dam on a normal diet, or rats kept on a normal fat diet after being birthed by a dam on a high fat (171).…”
Section: Animal Studiesmentioning
confidence: 99%